The Implementation of Animation Techniques in the 3D Animated Series Little Ammar, Season 4 Episode 03 - Putra, Abdul Hanif Lidia; Fris Okta Falma (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This final project report discusses the application of 3D animation techniques in the Little Ammar series, Season 04 Episode 03, with a primary focus on optimizing character expressions to appear more natural and communicative for a young audience. The project utilizes Blender software to implement various techniques such as advanced rigging, pose-to-pose animation, and the use of the Graph Editor. This approach aims to create expressive character movements that align with the narrative and match the child-friendly visual style. The production process includes stages ranging from storyboard planning, modeling, rigging, and animation to rendering and result evaluation. The results of the project demonstrate that techniques such as flexible facial expression controls, real video references, and classical animation principles such as anticipation, timing, and squash and stretch successfully enhance the visual quality and storytelling. Evaluation was conducted on both technical and narrative aspects, indicating the project's success in delivering animation that is not only aesthetically appealing but also effective in conveying moral messages. Technical challenges such as stiff motion transitions and difficulties in mimicking children's movements were successfully overcome through appropriate strategies, resulting in an animation that can be well enjoyed by children on the Durioo digital platform.